ANALISIS PENGENDALIAN PIUTANG TAK TERTAGIH BERDASARKAN UMUR PIUTANG TERHADAP KINERJA LAPORAN KEUANGAN PADA PT. LOUISZ INTERNATIONAL - Rizki Eka Putra; aznedra aznedra; sri mulyati (Universitas Riau Kepulauan, 2022)
Good receivable control system will affect the company’s success in carrying out the sale on credit policy. The credit sales are uncollectible risk of some or all credit extended to the debtor. As a result of theseuncollectible accounts receivable losses will cause the load, the company must determine the method that will be used to calculate the amount of the loss of this receivable. The study aims to analyze the control of bad debets based on receivable age on the performance of financial statements of PT. Louisz International and know the treatment of losses on bad debts of the company. The method used is descriptive method.The results showed that the internal control system of receivable at company has been effective, it can be seen from the implementation of elements of internal control of receivable eligible and supported by adequqte policies and procedures for theprovision of good credit. The company uses direct write off method in determining the bad debt. Direc write off method notes receivable really uncollectible receivables as bad debt. The companies manajemen should be used the aging schedule of allowance method to be more effective in determining damages for doubtful accounts. Keywors : Receivable, Internal Control System and Allowance Method